Avaliação do impacto de ações antrópicas sobre a comunidade de aves de áreas úmidas na região de domínio Mata Atlântica, Sul do Brasil - Heinz, Carolina de Mendonça (Universidade do Vale do Rio dos Sinos, 2011)
During the last decade science has paid a lot of attention to wetland bird preservation, this fact can be related to the frequent transformation of these environments in agroforestry monocultures. The articles presented are intended to estimate species richness of wetland birds present in some parts of the Araucarias plateau, estimating the diversity of bird community that inhabit the region and relate them to the landscape indices in order to understand how the community is affected by these changes and propose important areas for bird conservation in the Araucarias Plateau region. The study area for both articles covers the municipalities of São Francisco de Paula, Cambará do Sul, Jaquirana, Bom Jesus and Vacaria, including areas within the National Park Sierra de Aparados (PNAS). 26 areas were bounded considering the presence of wetlands with a surrounding field. Five areas were located in Cambará do Sul, six in Jaquirana, seven in Bom Jesus, five in Vacaria, and four in Aparados da Serra National Park (PNAS). Censuses were monthly conducted between September 2008 and April 2010. 68 wetland birds species were registered in Plateau region of Rio Grande do Sul. Were found as areas of greater richness some areas present in the municipalities of São Francisco de Paula and Vacaria. As areas of increased diversity, considering the Shannon index, were located in the municipalities of Vacaria and Cambará do Sul, with 3.046; 2.906 and 2.895 respectively. According to the Simpson index, areas were also present in the municipalities of Vacaria and Cambará do Sul. In relation to the parameters of the landscape we accepted the best model suggested by the program. In relation to the Shannon index we obtained the following results: influence of landscape, field, area of fragmentation and cohesion in the agriculture field, have a negative relationship with the diversity of birds. When considering the Simpsons diversity index, we found that landscape diversity and plated area have a positive relationship with the diversity of birds in question and agriculture cohesion presents a negative relationship with this index. For the second article we have as a regression result that the abundance of birds is influenced primarily by plant types, eringio, touceira and shrub, birds richness is directly influenced by the size of areas. The results found in habitat quality index (HSI) demonstrate that the areas D10, F14, D24, located in the municipality of São Francisco de Paula, JE7, located in the municipality of Jaquirana and VD56, located in the municipality of Vacaria show more favorable attributes for birds richness and abundance. With regard to endangered species and in accordance with the modeling we have seen that Xanthopsar flavus is distributed in the municipalities of São Francisco de Paula and Cambará do Sul Jaquirana, Vacaria, Xolmis dominicanus presents the same distribution. Limnoctites rectirostris presents itself distributed in municipalities of São Francisco de Paula, Jaquirana, Bom Jesus, Vacaria and Cambará do Sul. Scytalopus iraiensis had a restricted distribution, being present only in the Park Aparados da Serra, in the municipality of Cambará do Sul. Anthus nattereri this distributed in the municipalities of Cambará do Sul and São Francisco de Paula, Cinclodes pabsti presents a wide distribution, being present in the municipalities of São Francisco de Paula, Cambará, Jaquirana, Bom Jesus. Sporophila melonogaster in the municipalities of São Francisco de Paula, Cambará do Sul, Jaquirana and Vacaria. When we have grouped the areas according to the value of habitat quality index (HSI), the distribution of threatened species and species richness, we have as potential areas for conservation D10, F14, F17, Vd56 and Je6 present in the municipalities of São Francisco de Paula, Vacaria and Jaquirana respectively.
Keywords: Aves; Áreas úmidas; Conservação de aves; Sul do Brasil; Mata atlântica; Degradação ambiental; ACCNPQ::Ciências Biológicas::Biologia Geral